A liberdade sexual da mulher na prática judicial: análise da aplicação de esteriótipos de gênero em processos de estupro - Siqueira, Camilla Karla Barbosa (2017)
SIQUEIRA, Camilla Karla Barbosa. A liberdade sexual da mulher na prática judicial: análise da aplicação de esteriótipos de gênero em processos de estupro. 2016. 142 f. Dissertação (Mestrado em Direito) - Faculdade de Direito, Universidade Federal do Ceará, Programa de Pós-Graduação em Direito, Fortaleza, 2016. === Submitted by Vera Martins (vera.lumar@hotmail.com) on 2017-05-22T18:07:14Z No. of bitstreams: 1 2016_dis_ckbsiqueira.pdf: 1534492 bytes, checksum: 149b5fb08a48a318fb77ab42d4c1d8b1 (MD5) === Approved for entry into archive by Camila Freitas (camila.morais@ufc.br) on 2017-06-20T11:22:04Z (GMT) No. of bitstreams: 1 2016_dis_ckbsiqueira.pdf: 1534492 bytes, checksum: 149b5fb08a48a318fb77ab42d4c1d8b1 (MD5) === Made available in DSpace on 2017-06-20T11:22:04Z (GMT). No. of bitstreams: 1 2016_dis_ckbsiqueira.pdf: 1534492 bytes, checksum: 149b5fb08a48a318fb77ab42d4c1d8b1 (MD5) Previous issue date: 2016 === For centuries, women have been treated as inferior people, suffering because of this all kindsof violence. Despite the evolution brought by the era of recognition of rights, in both national and international level, including rights specifically designed for women, it is noticeable that they are still considered as inferior human beings in some level.This scenario causes the persistence ofgender-based violence, including sexual violence, which is adifficult problem to overcome nowadays. In the scenario described here, the study aims to investigate the persistent use of gender stereotypes in criminal rape cases. The Criminal Justice System is considered the legitimate arena for prevention of crime, and its effectiveness with regard to gender-based crimes needs to be investigated. In order to achieve this goal, the study first analyzed the concept of gender as a female emancipation tool and explored stereotypes related to gender. The next step consisted in researches around gender-based violence and its sexual form, including the investigation of rape as a crime in Brazilian law. It is argued that the Criminal Justice System, by incorporating gender stereotypes in their judgments, replicates the violence suffered by women, emerging as an institution incapable of protecting their sexual freedom, given that the gender violence is not slowing down. For the study, we used literature analysis, involving the reading of academic books and articles on the topics discussed, and documental analysis, mostly related to the examination of national and international normative documents, as well as criminal lawsuits that investigate crimes of rape committed against women, all of them originated .The approach is qualitative, and Critical Discourse Analysis isusedas a methodological tool for the lawsuit sanalysis, thus setting up a qualitative methodology. === Durante séculos, a mulher tem sido vista como ser inferior, sofrendo em razão disso violências de várias naturezas. Apesar dos avanços trazidos pela era do reconhecimento de direitos em âmbito nacional e internacional, inclusive direitos específicos das mulheres, percebe-se que a concepção inferiorizada do feminino ainda persiste no imaginário coletivo, tornando a violência de gênero, inclusive a de teor sexual, um problema difícil de contornar. Em virtude do cenário esboçado, o trabalho tem como objetivo principal investigara persistência do uso de estereótipos de gênero em processos penais de estupro.O Sistema de Justiça Criminal se põe como instância privilegiada de prevenção e reparação de crimes, e sua eficácia no que diz respeito aos crimes de gênero precisa ser averiguada. Para isso, foi analisado o conceito de gênero enquanto ferramenta de emancipação feminina, bem como o estudo de estereótipos relacionados ao gênero e da violência sexual como violência de gênero. Sustenta-se que o Sistema de Justiça Criminal, ao incorporar estereótipos de gênero em seus julgamentos, replica a violência sofrida pelas mulheres, surgindo como meio inábil para a proteção de sua liberdade sexual. Para a realização do estudo, utilizou-se análise bibliográfica, com análise de livros e artigos acadêmicos sobre os assuntos abordados, e documental, com o exame de normas nacionais e internacionais, bem como de processos judiciais em que se apurou o cometimento de crime de estupro contra mulheres, retirados do Judiciário cearense; a pesquisa é, portanto,restrita às práticas da Justiça do Ceará. A abordagem é predominantemente qualitativa. A Análise de Discurso Crítica foi usada como ferramenta metodológica para a análise processual. .